Cele długoterminowych decyzji finansowych - Gadawska, Jolanta (Wydawnictwo Uniwersytetu Wrocławskiego, 2010)
The main goal of the article is to characterise different types of financial decisions taken by companies, with special insight into long-term financial decisions. The article presents main theories of financial decisions, goals of financial management and types of decisions in financial management field. The main measures of the effectiveness of financial decisions are the cost of capital and the degree of leverage. The rate of return on invested capital must be higher than the cost of capital provided. Maximizing business value is the overriding long term goal of the decisions taken by its owners. Decisions made in companies are reviewed by the capital market. We can state that effectiveness of financial (capital) decisions depends on the efficiency of investment decisions, and vice versa. A basic condition for making rational decisions is a conduct in accordance with the objective function. Therefore, the new economic approach primarily aims to maximize the wealth of the owners, which means the company achieves the optimal level in particular circumstances
Keywords: decyzje finansowe; cele decyzji finansowych; skuteczność decyzji finansowych; gospodarka finansowa